THE INFLUENCE OF SHOPEE PAYLATER DIGITAL PAYMENTS TOWARDS SURABAYA SOCIETY'S CONSUMER BEHAVIOR - Dika Zaim Adhlan; Machsun; Iis Suryani (Suluh Adiluhung Publisher (SAPub), 2025)
This study aims to analyze the influence of the use of digital payments through Shopee PayLater on the consumer behavior towards Surabaya society. The research method used a quantitative method with a survey approach. Data were collected through questionnaires distributed to Surabaya society who use the Shopee PayLater service. Data analysis was carried out using statistical tests to determine the influence of the independent variable (use of Shopee PayLater) towards the dependent variable (consumer behavior). The results of the study showed that there was a significant influence between the use of Shopee PayLater on the consumer behavior of Surabaya society. The more often people use Shopee PayLater, the higher the level of consumer behavior shown. This is due to the ease of access and various promotions offered by Shopee PayLater, which encourage people to make purchases without careful consideration.